Antioxidant and antimicrobial applications of biopolymers: A review - Sivakanthan, S.; Rajendran, S.; Gamage, A.; Madhujith, T. (Elsevier, 2020)
Biopolymers have generated mounting interest among researchers and industrialists over the recent past. Rising consciousness on the use of eco-friendly materials as green alternatives for fossil-based biopolymers has shifted the research focus towards biopolymers. Advances in technologies have opened up new windows of opportunities to explore the potential of biopolymers. In this context, this review presents a critique on applications of biopolymers in relation to antioxidant and antimicrobial activities. Some biopolymers are reported to contain inherent antioxidant and antimicrobial properties, whereas, some biopolymers, which do not possess such inherent properties, are used as carriers for other biopolymers or additives having these properties. Modifications are often performed in order to improve the properties of biopolymers to suit them for different applications. This review aims at presenting an overview on recent advances in the use of biopolymers with special reference to their antioxidant and antimicrobial applications in various fields.
Keywords: Active packaging; Biodegradable polymers; Biomedicine; Environmental consciousness; Fossil fuels